The family structure in Islam - 'Abd al-'Ati, Hammudah (The Other Press Petaling Jaya, 2008)
"The Family Structure in Islam" examines the principles and values within Islamic teachings that guide family life, emphasizing roles, responsibilities, and the importance of mutual respect and harmony.